Biochar amendment as a remediation strategy for surface soils impacted by crude oil. (October 2020) - Mukome, Fungai N.D.; Buelow, Maya C.; Shang, Junteng; Peng, Juan; Rodriguez, Michael; Mackay, Douglas M.; Pignatello, Joseph J.; Sihota, Natasha; Hoelen, Thomas P.; Parikh, Sanjai J.
Abstract: The impact of organic bulking agents on the biodegradation of petroleum hydrocarbons in crude oil impacted soils was evaluated in batch laboratory experiments. Crude oil impacted soils from three separate locations were amended with fertilizer and bulking agents consisting of biochars derived from walnut shells or ponderosa pine wood chips produced at 900 °C. The batch reactors were incubated at 25 °C and sampled at pre-determined intervals to measure changes in total petroleum hydrocarbons (TPH) over time. For the duration of the incubation, the soil moisture content was adjusted to 75% of the maximum water holding capacity (MWHC) and prior to each sampling event, the sample was manually stirred. Results show that the addition of fertilizer and bulking agents increased biodegradation rates of TPH. Soil samples amended with ponderosa pine wood biochar achieved the highest biodegradation rate, whereas the walnut shell biochar was inhibitory to TPH biodegradation. The beneficial impact of biochars on TPH biodegredation was more pronounced for a soil impacted with lighter hydrocarbons compared to a soil impacted with heavier hydrocarbons. This study demonstrates that some biochars, in combination with fertilizer, have the potential to be a low-technology and eco-friendly remediation strategy for crude oil impacted soils. Graphical abstract: Image 1 Highlights: A pine biochar combined with fertilizer stimulated petroleum degradation in soils. That combination was relatively more effective for heavy than light crude oil. Biochar was more effective than wood chips. Biochar feedstock and pyrolysis conditions are important. Abstract : Biochar amendment is a viable remediation strategy for shallow soils contaminated by light and heavy weathered crude.